The Medication Related Burden Pada Pasien Hipertensi: Studi Kasus Di Apotek Afina Yogyakarta - Kurniawan, Rendy; Supadmi, Woro; Qifari Nasrun, Rahmar; Hastuti, Dwi (JURNAL FARMASI GALENIKA, 2024)
Hypertension is the cause of death in 31.5% (1.39 billion). The prevalence of hypertension is increasing in low- and middle-income countries. The prevalence of hypertension in Yogyakarta reached 35.8%, higher than the national figure (31.7%).  Hypertension requires long-term treatment which can cause a burden of treatment on patients. The purpose of this study was to determine the characteristics, treatment patterns and treatment burden of hypertension patients at Afina Pharmacy Yogyakarta. This study is an observational  descriptive approach. Data collection was carried out through direct interviews with patients about the burden of treatment with the Living With Medicine Questionaire (LMQ) questionnaire guide. The sample was in accordance with the inclusion and exclusion criteria totaling 31 respondents.  Data were analyzed using the descriptive  method.The results showed that 26 respondents (83.8%) were in the age group> 46 years, with 23 respondents (74.2%) of whom were female, the respondent's education level was at the SMA-PT level, namely 20 respondents (64.5), and 22 respondents (71%) had a previous history of hypertension.Based on patient therapy patterns, 22 respondents (70.9) used Calcium Channel Blocker class antihypertensives, namely Amlodipine and 18 respondents (58.1%) used Angiotensin Reseptor Blocker class antihypertensives, namely Candesartan 16 mg. Medication Related Burden of hypertension patients at Afina Yogyakarta Pharmacy is in the category of low burden 7 respondents (22.6%) and moderate burden 24 respondents (77.4%).